Wood combustion in a domestic stove: characterization of operating conditions and ashes produced - Tarelho, L.A.C. (2014)
Wood combustion in stoves for domestic heating purposes is a common practice in Portugal. However, some environmental impacts related to this practice are recognized, such as its effects on both indoor and outdoor air quality, and also those related to the management of the ashes produced. Results from an investigation about combustion of three wood varieties commonly used in Portugal in a batch-operated domestic stove are presented in this work. The wood fuels, the stove and the laboratorial facility developed to accomplish the measurements are described. Also, results from the continuous monitoring of the mass of the fuel batches undergoing combustion, the flow rate of the combustion air, the temperature in the combustion chamber and along the chimney, and the composition of the exit flue gas (O2, CO2, CO, total hydrocarbons) are presented. Ashes were collected from the grate of the stove after the combustion cycles and were characterised in regard to particle size distribution, chemical composition, mineralogy and leaching behaviour. The results from this investigation permit a better understanding about wood combustion and ashes produced in domestic stoves, which is needed for improving the performance of this type of equipments.